Effects of Uvaria rufa Blume on the Histology of Male Reproductive Organs of Testosterone Induced Alopecia Rats - Pamok, Supaporn (Microscopy and Microanalysis Research – The Journal of The Microscopy Society of Thailand, 2018)
Reports on the male reprotoxicity of some medicinal plants have been documented. This study was undertaken to evaluate the effects of ethyl acetate extract from the stems of Uvaria rufa Blume (UREtA) on the male reproductive organs of alopecia-induced rats. Androgenic alopecia (AP) was induced by testosterone propionate (0.07%). After hormonal injection, the rats were topically given vehicle (AP model), minoxidil, and 2% and 4% UREtA for 21 days. The normal control rats were given olive oil injections and received distilled water. The relative weights of the testes, epididymis, prostate glands, and epididymis, and histopathological alterations were examined. The results showed that testosterone injection reduced the relative weights of all organs when compared to those of the normal control, while significant decreases (P>0.05) were found only in epididymis and prostate glands. The increases in relative weights of epididymis observed in all treated groups, also testes and prostate glands observed in 4% UREtA and minoxidil, including seminal vesicles observed in 2% UREtA were clearly noted when compared to those of AP models. Vacuolizations were observed in testicular tissues treated with both concentrations of UREtA, while germ cell death in the lumens of the seminiferous tubules was seen in the minoxidil treated group. Dead spermatozoa in the lumens of the epididymis were markedly noted in all groups. Moreover, AP-induced rats treated with minoxidil revealed leucocyte infiltrations and blood congestions in their prostatic tissues. Therefore, it can be concluded that 2% and 4% UREtA has some adverse effects on male reproductive organs.